Fiancé & marriage visas : a couple's guide to U.S. immigration - Bray, Ilona M., 1962- (Nolo, 2025)
The book that's helped thousands of couples live in the U.S. together. You're engaged or married to a U.S. citizen or permanent resident, and all you want is the right to be together in the United States. Should be simple, right? It's not. The pile of application forms can be overwhelming, the bureaucracy isn't helpful, and delays are inevitable. This book will help you succeed. Discover the fastest and best application strategy. Avoid common--and serious--mistakes. Prepare for meetings with officials. Prove your marriage is real--not a fraud. Deal with the two-year testing period for new marriages. The 11th edition covers the latest, higher income requirements, easing of Trump-era regulations that put more immigrants at risk of being denied visas as a likely 'public charge,' and a new COVID vaccine requirement. It also provides handy checklists and illustrative sample forms. Use this book if you are living in the United States or overseas and your fiancé is a U.S. citizen, your spouse is a U.S. citizen, or your spouse is a U.S. permanent resident.